Molecular phylogeny and biogeography of the South American genus Metrodorea (Rutaceae) - Dias, Pedro; Udulutsch, Renata Giassi [UNESP]; Pirani, Jose Rubens (Tubitak Scientific & Technical Research Council Turkey, 2015)
The genus Metrodorea (Rutaceae), with 6 species, has representatives that vary from small shrubs to tall trees, and its leaf sheaths make it unique in the family; it is restricted to South America, with species diversity concentrated in Brazil. In this study, we applied Bayesian and parsimony methods to infer the molecular phylogeny of Metrodorea, and cladistic biogeographic methods to propose an area cladogram for the genus. All results supported Metrodorea as monophyletic, and the presence of leaf sheaths is reinforced as its key diagnostic feature. Bayesian and parsimony trees were identical for relationships within Metrodorea. The crown clade (M. flavida, M. mollis) is composed of two species of allopatric distribution and very different morphologies. Metrodorea is distributed in three biogeographic subregions: the Amazonian subregion is populated by one species, the Parana subregion by three species, and the Chacoan subregion by five species. Primary Brooks parsimony resulted in only one area cladogram, which differs from the strict consensus tree from the component analysis by the relationships of the Cerrado, and it suggests a closer relationship between Caatinga province and the Amazon subregion.
Keywords: Bayesian; parsimony; ITS; trnS-G; Brooks; component; biogeographic regions